RETRACTED: Optimization of Pyrolysis Parameters for Production of Biochar From Banana Peels: Evaluation of Biochar Application on the Growth of Ipomoea aquatica - Te, Wei Zun; Muhanin, Kavinesh Nair Manor; Chu, Yu-Ming; Selvarajoo, Anurita; Singh, Ajit; Ahmed, Shams Forruque; Vo, Dai-Viet N.; Show, Pau Loke (Frontiers in Energy Research, 2021)
Banana peels waste can be utilised to produce high quality biochar that can be incorporated into the soil for sustainable production of crops. This research analysed several properties of the biochar produced from the banana peel biomasses at different temperatures, residence times and heating rates. This study focuses on the biochar yield and the EDX analysis of the biochar produced. Response surface methodology using central composite design (CCD) was used to optimize these parameters in the batch reactor pyrolysis system. These factors were operated in different ranges for banana peels, in which pyrolysis temperature (200 to 600°C), residence time (60 to 180 minutes) and heating rate (5 to 15°C min-1) were varied using 20 experiments respectively. Quality of the biochar was determined based on the biochar yield and O/C ratio. The optimum biochar chosen from the CCD model was applied to several pots of Ipomoea aquatica in different biochar dosage levels of 0, 3, 9 and 15 g (0, 1, 3 and 5 wt% of soil) respectively. Pot experiment was conducted with completely randomized design (CRD) of one factor with 5 replications to correlate the average plant heights with the biochar dosage levels. Results showed that biochar dosage of 1% yields the highest average final Ipomoea aquatica plant height of 37.04 cm, while the plants with biochar dosage of 5% wilted.